1989
DOI: 10.1002/chin.198942139
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Structure and Ambident Reactivity of Phenylpemoline.

Abstract: Methylation of the phenyliminooxazolidinone (I) gives a mixture of the (methylphenylamino)oxazolinone (III) and the 3‐methyloxazolidinone (IV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Experimental studies on the amino-imino tautomerism of 2-aminothiazolidine-4-one have been reported in several papers. [2][3][4][5][6][7][8][9][10][11][12][13][14] However, the opinions of the authors are contradictory. Amirthalingam and Muralidharan 7 have confirmed by X-ray the existence of the imino form of pseudothiohydantoin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies on the amino-imino tautomerism of 2-aminothiazolidine-4-one have been reported in several papers. [2][3][4][5][6][7][8][9][10][11][12][13][14] However, the opinions of the authors are contradictory. Amirthalingam and Muralidharan 7 have confirmed by X-ray the existence of the imino form of pseudothiohydantoin.…”
Section: Introductionmentioning
confidence: 99%
“…By means of IR spectroscopy, Khovratovich and Chizhevskaya 5 have shown that in chloroform solution the amino form exists. According to Ramsh et al 11 (IR and NMR data), in DMSO and in water solutions pseudothiohydantoin exists as amino tautomer. Studies 13 of 2-aminothiazolidine-4one and its isomer 4-aminothiazolidine-2-one have been carried out by IR and 1 H and 13 C NMR spectroscopy in DMSO solution and have shown that 2AT exists in amino form while 4AT in imino form.…”
Section: Introductionmentioning
confidence: 99%